Three-dimensional imaging in maxillofacial and plastic surgery - Bogusiak, Katarzyna; Kociński, Marek; Materka, Andrzej; Arkuszewski, Piotr; Przygoński, Aleksander (Journal of Stomatology, 2016)
Recent advances in technology have made threedimensional imaging and analysis possible. Different three-dimensional technologies such as 3-D cephalometry, morphoanalysis, moiré topography, multislice CT-assisted imaging, cone beam CT and MRI scanning, 3-D laser scanning and photographic modalities have been developed. None of these imaging techniques can alone capture and represent the true relationship between facial skeleton, soft tissue and dentition. Only image fusion models of different imaging techniques can create a 3-D virtual head displaying all of these elements. On the basis of such accurate 3-D face/head reconstruction a realistic prediction model of soft and hard tissues changes can be created.